Unilateral Biportal Endoscopy for Decompression of Extraforaminal Stenosis at the Lumbosacral Junction: Surgical Techniques and Clinical Outcomes - Park, Man-Kyu; Son, Sang-Kyu; Park, Weon Wook; Choi, Seung-Hyun; Jung, Dae Young; Kim, Dong Han (Neurospine, 2021)
Objective: The aims of this study were to describe the unilateral biportal endoscopic (UBE) technique for decompression of extraforaminal stenosis at L5–S1 and evaluate 1-year clinical outcomes. Especially, we evaluated compression factors of extraforaminal stenosis at L5–S1 and described the surgical technique for decompression in detail.Methods: Thirty-five patients who underwent UBE decompression for extraforaminal stenosis at L5–S1 between March 2018 and February 2019 were enrolled. Clinical results were analyzed using the MacNab criteria, the visual analogue scale (VAS) for back and leg pain, and the Oswestry Disability Index (ODI). Compression factors evaluated pseudoarthrosis within the transverse process of L5 and ala of sacrum, disc bulging with or without osteophytes, and the thickened lumbosacral and extraforaminal ligament.Results: The mean back VAS was 3.7 ± 1.8 before surgery, which dropped to 2.3 ± 0.8 at 1-year postoperative follow-up (p < 0.001). There was a significant drop in postoperative mean VAS for leg pain from 7.2 ± 1.1 to 2.3 ± 1.2 at 1 year (p < 0.001). The ODI was 61.5 before surgery and 28.6 (p < 0.001). Pseudoarthrosis between the transverse process and the ala was noted in all cases (35 of 35, 100%). Pure disc bulging was seen in 12 patients (34.3%), and disc bulging with osteophytes was demonstrated in 23 patients. The thickened lumbosacral and extraforaminal ligament were identified in 19 cases (51.4%). No complications occurred in any of the patients.Conclusion: In the current study, good surgical outcomes without complications were achieved after UBE decompression for extraforaminal stenosis at L5–S1.